1979
DOI: 10.1111/j.1532-5415.1979.tb04139.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization and Prescribing Patterns in a Skilled Nursing Facility: The Need for a Rational Approach to Therapeutics

Abstract: A study was made of 50 patients drawn at random from a Skilled Nursing Facility (SNF) attended by seven physicians. For 59 percent of these patients, polypharmacy was practiced but no substantiating diagnoses were recorded. Approximately half of the drugs were administered pro re nata. More drugs were prescribed in potentially toxic dosages than in subtherapeutic dosages. The risk of an adverse drug reaction (ADR) was most often associated with anticholinergic agents, sedative-hypnotic drugs, and neuroleptics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…However, data from nursing facility research have indicated a strong association between adverse drug reactions and the lack of a definite diagnostic indication. 30 Whether this is true also for residents of RCFEs warrants further investigation. In any event, the absence of diagnoses in the health record made it very difficult, if not impossible, to evaluate the appropriateness of prescribing or medication use.…”
Section: Research Reportsmentioning
confidence: 98%
“…However, data from nursing facility research have indicated a strong association between adverse drug reactions and the lack of a definite diagnostic indication. 30 Whether this is true also for residents of RCFEs warrants further investigation. In any event, the absence of diagnoses in the health record made it very difficult, if not impossible, to evaluate the appropriateness of prescribing or medication use.…”
Section: Research Reportsmentioning
confidence: 98%
“…Kalchthaler et al 1977;Segal et al 1979;Ray et al 1980;Clarke et al 1981;Beers et al 1988;Buck 1988;Burns et al 1988;Beardsly et al 1989). The rates of psychotropic drug intake reported from these studies lie between 32 % (Burns et al 1988) and 86% (Segal et al 1979). Of the different types of psychotropic drugs, most studies indicated that neuroleptics or hypnotics were used most frequently, while the use of antidepressants and anxiolytics was less common.…”
Section: Introductionmentioning
confidence: 94%
“…Care of the elderly living in long‐term institutions has attracted much attention in the United States. Numerous studies on prescribing for this tiny sector of the community (less than 5% of all persons aged 65 years or older) have been published 36–49 …”
Section: Prescribing For the Elderly In Long‐term‐care Institutionsmentioning
confidence: 99%